PERAN BALAI PENGELOLAAN HUTAN MANGROVE WILAYAH I BALI DALAM PENGOLAHAN HASIL HUTAN MANGROVE BERBASIS PEMBERDAYAAN MASYARAKAT LOKAL - Komang Dean Ananda; Pande Komang Suparyana; Maftukhakh Hilmya Nada (SOCA: Jurnal Sosial Ekonomi Pertanian, 2019)
Mangrove degradation is increasing along the proliferation of purposely land conversion. The utilization of the products of mangrove forests are oriented to the timber. Processing of mangrove products that have economic value should be a form of mangrove conservation and sustainability. Balai Pengelolaan Hutan Mangrove (BPHM) Wilayah 1 Bali, has become a center to processing mangrove forest products, especially non-timber products in Mangrove Tahura Ngurah Rai, which empowers local communities with skill training to process mangrove products into the economic value products. This research was carried out at the Mangrove Tahura Ngurah Rai. The method used is by observing mangroves by random sampling which will then be harvested based on the characteristics of ready harvest and harvest time. Mangroves that have been harvested, among others Sonneratia caseolaris, Bruguiera gymnorrizha, and Xylocharpus granatum. Those mangrove products will be processed into products such as syrup, soap, dodol, flour, rice, and scrubs. The processing of non-timber products is done through empowering local communities. The utilization of mangroves is more focused on the non-timber of forest products by utilizing mangrove fruits and leaves, ecotourism utilization, and silvofishery. BPHM I. Bali has an important role in maintaining the sustainability of the Mangrove Tahura Ngurah Rai.